Strategi Optimalisasi Media Sosial Marketing Dalam Meningkatkan Brand Awareness dan Penjualan Batik Putri Sanggabuana Karawang - Pribadi, Rizky Ahmad; Sihabudin; Fauji, Robby (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to analyze social media optimization strategies in increasing Brand awareness and sales of Batik Putri Sanggabuana Karawang. Using a qualitative approach with a case study method, this research explores the effectiveness of social media platforms such as Instagram and Facebook in promoting local products. The results show that the use of attractive, educative, and consistent visual content is able to increase public awareness of Batik Putri Sanggabuana. Promotion through social media, including paid advertisements, has proven effective in increasing sales by up to 20%. Nonetheless, challenges such as maintaining content quality and attracting the attention of young audiences are key focuses that need to be addressed. Active interaction with consumers through social media also contributes greatly to building customer loyalty. This study recommends a more structured and creative marketing strategy to expand market reach and strengthen the image of Batik Putri Sanggabuana as Karawang's local cultural identity.